On the best quadrature formulas for some classes of continuous functions - Polyakov, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We obtain the best quadrature formulas for classes of continuous functions defined by various restrictions on the moduli of continuity with respect to increase and decrease.